2011
DOI: 10.1242/jcs.085340
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for neural cell adhesion molecule in modulating insulin signaling and adipocyte differentiation of mouse mesenchymal stem cells

Abstract: SummaryNeural cell adhesion molecule (NCAM) has recently been found on adult stem cells, but its biological significance remains largely unknown. In this study, we used bone-marrow-derived mesenchymal stem cells (MSCs) from wild-type and NCAM knockout mice to investigate the role of NCAM in adipocyte differentiation. It was demonstrated that NCAM isoforms 180 and 140 but not NCAM-120 are expressed on almost all wild-type MSCs. Upon adipogenic induction, Ncam -/-MSCs exhibited a marked decrease in adipocyte dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 53 publications
5
26
0
Order By: Relevance
“…The Ncam −/− (knockout; KO) mice were generated on a C57/BL6 background as previously described . Wild‐type (WT) and KO MSCs were obtained from 8‐week‐old male mice as previously described . Briefly, cells were harvested from mouse bone marrow and cultured in low glucose Dulbecco's modified Eagle's medium (DMEM‐LG) containing 10% FBS, 100 IU/mL penicillin and 100 g/mL streptomycin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Ncam −/− (knockout; KO) mice were generated on a C57/BL6 background as previously described . Wild‐type (WT) and KO MSCs were obtained from 8‐week‐old male mice as previously described . Briefly, cells were harvested from mouse bone marrow and cultured in low glucose Dulbecco's modified Eagle's medium (DMEM‐LG) containing 10% FBS, 100 IU/mL penicillin and 100 g/mL streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…NCAM is also expressed in MSCs, but its function remains largely unknown. We have previously demonstrated that NCAM promotes adipocyte differentiation of murine MSCs via PI3K‐Akt pathways . NCAM is also involved in chondrogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fate of HSCs is regulated by small molecules that promote self-renewal [181][182][183] . Using small molecules, multipotent MSCs can differentiate into various non-hematopoietic cells, such as chondrocytes [134,184] , osteoblasts [185,186] , hepatocytes [187] , cardiomyocytes [188,189] , adipocytes [190,191] and neuronal-like cells [192][193][194] . Additionally, the maintenance of MSCs is associated with the Wnt signaling pathway [195,196] .…”
Section: Small Molecules and Stem Cell Fatementioning
confidence: 99%
“…Even though cell-substrate adhesion modulating proteins are classically described to be important for cell migration it becomes increasingly apparent that these molecules can have a wide range of additional functions [1-3]. Vice versa, numerous proteins identified earlier as being involved in adhesion- or migration-unrelated cellular events are increasingly being recognized to also modulate cell attachment, spreading or migratory behavior of cells [4-6].…”
Section: Introductionmentioning
confidence: 99%